Is Balance of Payments a monetary phenomenon: doctrinal aspects and empirical evidence from India - N. KUBENDRAN; Rose Govindha RAJ; Balaram ROULA (Theoretical and Applied Economics, 2025)

(untitled)
The main aim of the study is to test the relevance and effectiveness of Harry Johnson’s monetary approach using the Balance of Payments Account and Money supply in India. The study uses annual data from 1991 to 2024, especially since the execution of LERMS in 1991. This study uses the Augmented Dickey-Fuller and Philips-Perron test for stationary conditions. In order to detect the automatic equilibrium process under a flexible exchange rate system and to analyse the short-run and long-run relationship, the study employed the Autoregressive Distributed Lag-Error Correction Model (ARDL-ECM) for analysis. The test results from the ARDL model depict that there is a long-run association between BOP and independent variables like Exchange rate, money supply and capital outflows. ARDL-ECM model did not find any causality in the short run. Also, the study did not find any automatic restoration process in India’s Balance of Payments since LERMS. So this study found less relevance of the monetary approach in solving disequilibrium in India’s Balance of Payments. Also, the study observed that the role of monetary policy is not effective in the context of India’s BOP. In the present scenario, this may not be an issue for an emerging economy like India. But in the long run, to achieve external equilibrium based on the Mundell-Flemings assignment rule, the study strongly recommended Friedman’s monetary rule for the effectiveness of the monetary policy.